A Force-based Method for the Numerical Simulation of a Reinforced Concrete Shear Wall Building - Nawel, Benlaala; Kadid, Abdkrim; Yahiaoui, Djarir (Engineering, Technology & Applied Science Research, 2023)
Reinforced Concrete (RC) shear walls are structural elements that resist lateral loads. This research aims to present the numerical modeling of RC shear walls in order to evaluate the seismic performance of structures. Various types of numerical models of RC frame elements are implemented in nonlinear analysis packages. These numerical models are based on different theories and assumptions, something that poses a significant difficulty to practicing engineering and limits confidence in the analysis of the numerical results. In this study, inelastic force-based elements and distributed plasticity methods are used for the modeling of the inelastic behavior of these elements (infrmFB). The efficiency of the inelastic force-based element and distributed plasticity method is evaluated through the comparison with the experimental results of a shear wall structure subjected to seismic loadings. The accuracy of the numerical model is assessed in terms of top displacement, inter-story drift, base shear force, and the absolute maximum values of the overturning moment.